Microjazz - Norton, Christopher 1953- (Colecction, 2015)
Microjazz helps you develop musicianship and technique through the familiar sounds and styles of popular music. It is this unique combination of modern genres with traditional technique that has made Microjazz an international success with teachers and players, and one of the most widely used educational series ever published. New technology brings Microjazz alive and adds an exciting interactive dimension to practice and performance. A 3.5" standard midi file disk is available for many of the Microjazz books, providing high quality orchestrations of all the pieces.